WEIGHTING THE RISKS FOR NUCLEAR POWER PLANTS USING AHP AND ANP METHODOLOGIES - Ozdemir, Yavuz; Tuysuz, Suat; Basligil, Huseyin (YILDIZ TECHNICAL UNIV, 2016)
Risk assessment and management of nuclear power plants is a difficult process. This process is pretty much the reason why it is difficult is that the number of the variable is unclear. To resolve this problem, in the sense of verbal and quantitative are not sufficient to implement the security management system security risk assessment is also essential in today'sworld has become. Criteria for the evaluation of nuclear facility security risk assessment instrument in ourwork, the Analytical Hierarchy Process (AHP) and Analytic Network Process (ANP) was established through preliminary evaluation in the evaluation methods through the use of the theory of. As a result of the finding sobtainedand comparisons were made between there sults of the evaluation methods. Benefited from these methods and the evaluation indicator information item sand the effects of a consistent estimate of the status of a nuclear power plant safety has become available for sustenance.
Keywords: AHP; ANP; Nuclear energy; Risk assessment; Engineering